Situs Inversus Totalis: Single-Stage Anatomic Repair of Complex Congenital Heart Disease. Issue 2 (March 2018) - Chatzis, Andrew C.; Tsoutsinos, Alexandros J.; Kanakis, Meletios A.; Contrafouris, Constantinos A.; Rammos, Spyros; Mitropoulos, Fotios A.
Transposition of the great arteries occurs rarely in patients with mirror image dextrocardia and situs inversus, while the combination with severe coarctation of the descending aorta (CoA) makes the anatomy even more unusual. Therefore, it is not surprising that a case with such unusual and complicated anatomy presents unique problems when a primary definitive correction is attempted. We report a patient with situs inversus totalis and complex congenital heart disease including transposition of the great arteries and severe CoA who underwent successful complete, single-stage, anatomic correction.